Age-related biomechanical variations in vertical jumping and sprinting performance among basketball players - Petrovic, Milos; Ramos, Jorgelina; Hafsteinsson, Thrainn; Gisladottir, Thordis (Frontiers in Sports and Active Living, 2025)
IntroductionThis study aims to investigate age-related differences in physical performance metrics, specifically vertical jumping and sprinting capabilities, between young (average age 12.5) and senior (average age 23.2) male basketball players.MethodsPerformance metrics were assessed through standardised tests measuring jump height and sprint times, alongside force production during eccentric and concentric phases of jumping movement.ResultsKey findings show that senior players outperform younger athletes in both sprint times and jump heights, attributed to greater physical maturation and neuromuscular development. However, contraction times and phase durations were similar across both age groups, indicating that strength improvements do not affect fundamental movement timing.DiscussionThese results highlight the importance of age-specific training programs that focus on developing explosive power for younger players and optimising performance while minimising injury risk for seniors. The study provides valuable insights and recommendations for tailoring training strategies to athletes' developmental stages and suggests that further research is needed to explore effective interventions for enhancing physical performance across the lifespan.